The Severity Measurement of Chronic Venous Insufficiency in Patients with Type 2 Diabetes Mellitus Using Duplex Sonography - Budiman, Muhamad Arif; Madiastuti, Septi; Nanang, Fitry Rahayu (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Chronic Venous Insufficiency (CVI) is a long-term condition that affects the veins in the legs, disrupting the blood flow to the heart. It is more common in patients with type 2 Diabetes Mellitus as it is one of the risk factors. Patients with CVI and a history of Type 2 Diabetes Mellitus may experience various symptoms depending on the severity of their condition. The severity of chronic venous insufficiency (CVI) was assessed in three patients from Cibinong Regional General Hospital with a history of type 2 diabetes using duplex sonography. According to the results, Patient I was diagnosed with moderate severity of CVI in the left leg (500 msec) and mild in the right (330 msec). Patient II was identified with moderate severity in both legs (430 msec left, 460 msec right). Patient III was found to have severe severity in both legs (750 msec left, 760 msec right). Patient I, who has mild-moderate chronic venous insufficiency (CVI) and a history of type 2 diabetes mellitus, experiences swollen feet, changes in skin texture, pitting edema, and a sense of heaviness and numbness in their legs. Patient II, who has moderate CVI, suffers from swollen legs, diabetic ulcers, pitting edema, discomfort and numbness in their legs, and skin discoloration. Patients III with severe CVI suffer swelling in both legs, pitting edema, venous dermatitis, ulcers, and numbness in their legs during activities and at night. Compression bandage treatment is recommended for patients who have moderate and severe CVI and a history of type 2 diabetes.